POSITIVE CT BRAIN DURING EARLY POSTOPERATIVE PERIOD IN HEAD INJURY PATIENTS: IMPACT ON CLINICAL COURSE AND OUTCOME - Rehman, Zia ur; Khan, Muhammad Mukhtar; Ayub, Shahid (Journal of Postgraduate Medical Institute, 2017)
Objectives: To assess the impact of positive postoperative CT head during the initial 72 hours on overall clinical course and outcome. Methodology: 157 patients of head trauma who underwent cranial surgery were prospectively included. All patients underwent a repeat head CT during the initial 72 hours or as was indicated by neurological status of the patient. Data was collected about patient demographics, initial CT diagnosis, repeat CT findings, re-operation if performed, GCS at discharge, mortality and outcome in terms of GOS. Data was analysed for impact of positive finding in postoperative CT head and its impact on clinical course and outcome. Results: The overall mean age was 34.25 ±11.59 years with a mean arrival GCS of 9.2 ±2.32. The mean time to first postoperative CT was 21.45 ±9.83 hours. The postoperative CT scan was positive in 29 (18.5%) patients in which 16 (10.2%) cases required re-intervention. Overall mortality was 19 (12.1%), of which 9 (44.1%) had a positive post-operative CT scan and 4 (21.1%) of them underwent a repeat intervention. 2.3% of patients with negative CT were re-operated while 44.8% were re-operated in the positive CT (p <0.0001). Similarly, mortality was 7.8% in the negative CT group while it was 31.0% in the positive CT group (p <0.0001). Conclusions: Positive follow-up CT scan during early post-operative period can affect significantly the clinical course and neurological outcome of patients.